Efisiensi Produktifitas Wakaf Tunai (Wakaf Uang) dalam Pemberdayaan Ekonomi di Indonesia - Saadati, Nila (Muqtasid: Jurnal Ekonomi dan Perbankan Syariah, 2016)
This article aims to analyze the waqf if it is managed productively. Commonly, the existence of waqf in Indonesia is used for the mosque, school, farm, and orphanages. Thus, the existence of cash waqf is productive if it can be a solution for the community to improve the economy of the people as a form of solidarity that becomes an instrument contributed to the welfare of society